2020
DOI: 10.1242/dev.170829
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling is essential for sustaining proximo-distal progression in regenerating axolotl limbs

Abstract: Amputation of a salamander limb triggers a regeneration process that is perfect. A limited number of genes have been studied in this context and even fewer have been analyzed functionally. In this work, we use the BMP signaling inhibitor LDN193189 on Ambystoma mexicanum to explore the role of BMPs in regeneration. We find that BMP signaling is required for proper expression of various patterning genes and that its inhibition causes major defects in the regenerated limbs. Fgf8 is downregulated when BMP signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 65 publications
0
46
0
Order By: Relevance
“…Validation studies show that mCherry is exclusively detectable in the distal-most part of the limb bud/ blastema during development and regeneration (Supplementary Fig. 10), labelling the field that gives rise to the hand segment in accordance with the model of progressive specification 23,27 , thus offering the means to genetically identify blastema cells that have been specified to a distal fate based on their fluorescence. Upon appearance of the cohort of mCherry + distal cells in the regenerating limb, we electroporated Tig1 or Tig1 P155A T2A-GFP constructs, FACS sorted mCherry + /GFP + (distal cells overexpressing Tig1) and mCherry + /GFP - (distal control cells) cells at 3 or 8 days post electroporation, and performed bulk RNA sequencing analysis (Fig.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Validation studies show that mCherry is exclusively detectable in the distal-most part of the limb bud/ blastema during development and regeneration (Supplementary Fig. 10), labelling the field that gives rise to the hand segment in accordance with the model of progressive specification 23,27 , thus offering the means to genetically identify blastema cells that have been specified to a distal fate based on their fluorescence. Upon appearance of the cohort of mCherry + distal cells in the regenerating limb, we electroporated Tig1 or Tig1 P155A T2A-GFP constructs, FACS sorted mCherry + /GFP + (distal cells overexpressing Tig1) and mCherry + /GFP - (distal control cells) cells at 3 or 8 days post electroporation, and performed bulk RNA sequencing analysis (Fig.…”
Section: Introductionmentioning
confidence: 95%
“…5f). Among these are bone morphogenetic proteins (BMP) Bmp2 and Bmp7, important for sustaining progressive regeneration and formation of distal elements 27 . In addition, elevated Tig1 levels promote the downregulation of morphogenetic factors associated with blastema growth and patterning, including Lhx9, Lmo1, Spry1 and Lhx2 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Here, BMP activates apoptosis in the apical ectodermal ridge and the limb mesenchyme (Gañan et al, 1998;Guha et al, 2002). BMP signaling is also required for regeneration of axolotl limbs (Guimond et al, 2010;Vincent et al, 2020). In this system, the regulation of apoptosis by BMP2 appears to function the same for both the developing and regenerating limb (Guimond et al, 2010).…”
Section: Initiation and Regulation Of Regenerative Apoptosismentioning
confidence: 99%
“…In a recent study our group showed that Bmp2 is not the only Bmp that is upregulated during limb regeneration but that Bmp5 and Bmp7 are also active (n.b. we could not clone axolotl Bmp4 so it was not looked at, but the genome sequencing revealed that it is not present in axolotls 97 ) 12 .…”
Section: -Bmp To End (Redifferentiation/redevelopment Phase)mentioning
confidence: 99%
“…The re-development phase of limb regeneration is, as the name indicates, very similar to limb development. Pattern formation becomes evident as the different tissues that compose the limb start appearing, and many genes are expressed in a similar pattern between limb regeneration and development [12][13][14][15] . Of course it is difficult to draw absolute lines as to when exactly the preparation and redevelopment phases become distinct.…”
Section: Introductionmentioning
confidence: 99%